2013
DOI: 10.4081/ija.2013.e20
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Physical Quality of Tilled and No-Tilled Soils in an Almond Orchard in Southern Italy

Abstract: No-tillage (NT) is an alternative way of reducing costs and lessening the burden of working the land, but in essence it is a method of sustainable land use in dryland cropping systems. The physical quality of the soil is the fundamental factor that defines the sustainability of agro-ecosystems, and its evaluation can be obtained using both capacitive and dynamic indicators. The main objectives of this study were: i) to assess the physical quality of the soil in an almond orchard where long-term different soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 45 publications
1
23
1
1
Order By: Relevance
“…It has been reported that PAWC and S‐index vary over time, and the relationship with soil bulk density adequately can explain such trends. In our study, the first relationship was always negative for all sampling date (S‐index decreases as BD increases), confirming what has been reported in literature (Castellini et al ., ). However, the relationship PAWC‐BD showed both positive and negative trends (Figure ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…It has been reported that PAWC and S‐index vary over time, and the relationship with soil bulk density adequately can explain such trends. In our study, the first relationship was always negative for all sampling date (S‐index decreases as BD increases), confirming what has been reported in literature (Castellini et al ., ). However, the relationship PAWC‐BD showed both positive and negative trends (Figure ).…”
Section: Resultsmentioning
confidence: 97%
“…Probably, the positive effects of OC on improving of soil structure were counterbalanced by the clayey matrix of soil that represents the most important factor for soil structural stability (Dexter, ). Our results suggest that when a set of soil physical quality indicators was chosen, the related results should be interpreted with caution, because it is rare for all the indicators to agree (Castellini et al ., ). Even though our study only considered two types of soil management practice, the results are consistent with those reported by Reynolds et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…These indicators were macroporosity (P mac = u s À u m ) (L 3 /L 3 ), air capacity (AC = u s À u FC ) (L 3 /L 3 ), plant available water capacity (PAWC = u FC À u PWP ) (L 3 /L 3 ) and relative field capacity (RFC = u FC /u s ), where u m , u FC , u PWP are the volumetric water content corresponding to h = À10, À100 and À15300 cm, respectively. Some reference values for these capacitive indicator as described in the literature were also considered, in order to evaluate whether the modifications induced by biochar addition led to an improvement or a worsening of the physical properties of the soil (Castellini et al, 2013). A brief review can be found in Reynolds et al (2009).…”
Section: Volumetric Water Retention Capacitive Indicators and Dry Bumentioning
confidence: 99%